PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN PENEMPATAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN TETAP DI KOPERASI WARGA SEMEN GRESIK (KWSG) - Devi Oktavia Puspita Sari (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
The purpose of this study to determine the effect of work motivation, work environment and job placement on the morale of permanent employee of Semen Gresik Cooperative. The sample uses the proportionate stratified random sampling method which is a sampling technique when an organization has employees from the background of stratified positions totaling 106 people. Data analysis techniques use multiple linear regression. The result of multiple linear regression analysis proves that the work motivation, work environment and job placement have a significant effect on the morale of permanent employee of Semen Gresik Cooperative.